CONNOTATIVE MEANINGS AS MUSLIM IDENTITY IN ZOHRAN MAMDANI’S SPEECHES - Sabrina Satriawati; Ruminda; Fourus Huznatul Abqoriyyah (Universitas Gunadarma, 2026)
This study investigates connotative meaning in Zohran Mamdani’s speeches and its relation to Muslim identity. It addresses the limited discussion of how connotative meaning functions in political discourse, particularly in relation to minority identity. This study aims to identify positive and negative connotative meanings and explain how they relate to the expression of Muslim identity. Using a qualitative descriptive method, the study analyzes 13 lexical items selected from two speeches delivered in different political contexts. The analysis is based on Leech’s (1981) theory of connotative meaning and Joseph’s (2004) view of language and identity. The findings show that 6 lexical items carry positive connotations, reflecting affirmation, dignity, belonging, visibility, and solidarity, while 7 lexical items carry negative connotations, indicating marginalization, stigma, prejudice, and social pressure. The study finds that connotative meaning is closely related to identity because it shows how Muslim identity is expressed, experienced, and understood through lexical choices. Overall, the study suggests that speech is not only used to deliver messages, but also to shape identity within a broader social context.